The tumor microenvironment in leukemia: molecular pathways of immune evasion - Zhu, Ying; Liu, Jinying; Qiu, Fang; You, Zhongjian; Liu, Zhirui; Zeng, Jiqiang; Zhong, Jinqiong; Song, Ziling; Zhang, Shanrong; Lu, Jiawei; Jiang, Yujie; Liu, Jianshuo; et al. (Frontiers in Immunology, 2026)
The interplay between the immune system and leukemia presents major challenges to effective therapy development. This Review examines mechanisms of immune evasion across leukemia subtypes, emphasizing T-cell exhaustion, regulatory T cells (Tregs), and antigen-presentation deficits. Globally, leukemia remains a significant burden, with approximately 460,000 new cases and 320,000 deaths estimated in 2021 alone. Recent studies reveal how the tumor microenvironment (TME) shapes immune behavior and how leukemic cells remodel it to support survival and therapeutic resistance. We illustrate these adaptive processes, highlighting the contributions of the bone-marrow niche and B-cell dysregulation in chronic lymphocytic leukemia (CLL). We further discuss implications for immunotherapy, noting that agents like magrolimab (anti-CD47) combined with azacitidine have demonstrated objective response rates (ORR) exceeding 80% in early-phase AML trials, though challenges such as on-target anemia persist. By integrating current evidence from preclinical metabolic profiling to Phase 3 clinical data on E-selectin inhibition (uproleselan)—we clarify the immune landscape of leukemia and outline avenues for innovative treatments. Ultimately, this Review underscores the need for multifaceted immunotherapeutic approaches that account for the complex interactions within the TME.